Influence of pressure on elasticity, mechanical properties, and Li diffusion in battery electrode material LiCoO2: First-principles calculations - Wutthigrai Sailuam; Ittipon Fongkaew; Wutthikrai Busayaporn; Rakchat Klinkla; Kanoknan Phacheerak (Results in Physics, 2023)
This study used first-principles calculations based on density functional theory with generalized gradient approximation (GGA) of the Perdew Burke and Ernzerhof (PBE) parameterized form to investigate the influence of pressure on the structural, elastic, and mechanical properties of rhombohedral LiCoO2. The results indicate that rhombohedral LiCoO2 remains stable up to 10 GPa. The calculated ground state properties agree well with experimental and other calculation data, validating the approach. Additionally, the calculated elastic constants, bulk modulus, Young's modulus, shear modulus, and Poisson's ratio at 0 GPa agree with previous results. The study found that all elastic constants continuously increase with increasing pressure. The deformation resistances along the axial direction are stronger than those in shape. The relationship between elasticity and length is such that C11 > C33, indicating that the incompressibility along the a axis is stronger than that along the c axis. The analysis of Poisson's ratio (ν) and Pugh's criterion B/G strongly suggests that rhombohedral LiCoO2 exhibits ductile behavior under pressure up to 10 GPa. The material is clearly anisotropic behavior, but the material exhibits improved isotropic behavior as pressure increases. Regarding Li ion diffusion in rhombohedral LiCoO2, the study found that the migration pathway for Li ions in rhombohedral LiCoO2 is a direct route that extends from the VLi site to the closest Li site. The diffusion process is hindered by a diffusion energy barrier of 0.87 eV, which is in good agreement with available theoretical data. Furthermore, the Li ion diffusion energy barrier increases with pressure because the decrease in dmean and polyhedral volume, along with changes in angle and torsional distortion factors of CoO6 octahedra, which can reduce the charging and discharging speeds of Li-ion batteries that use rhombohedral LiCoO2 as the cathode material.
Keywords: Advancements in Battery Materials; Advanced Battery Technologies Research; Advanced Battery Materials and Technologies